125I seed implantation for lymph node metastasis from radioactive iodine-refractory differentiated thyroid carcinoma: a study on short-term efficacy and dosimetry - Zhang, Wenwen; Hao, Shanhu; Wang, Zhiguo; Ding, Tingting; Zhang, Guoxu (Frontiers in Oncology, 2024)
Objective To investigate the feasibility and evaluate the safety and effectiveness of Computed Tomography (CT) guided125I radioactive particle implantation for treating lymph node metastases in radioiodine-refractory differentiated thyroid cancer (RAIR-DTC). To verify the accuracy of the computerized three-dimensional treatment planning system (TPS) in treating lymph node metastasis using125I particle implantation at the dosimetric level. Methods A retrospective analysis was conducted on 42 patients with RAIR-DTC and lymph node metastases who were admitted to the General Hospital of the Northern Theater Command between December 2016 and January 2019. During this analysis, physicians utilized preoperative CT images to design an intraoperative plan using TPS. The dosimetric parameters of the postoperative plan were then compared to the preoperative plan. Additionally, this study examined the changes in tumor size and tumor-related marker Thyroglobulin (Tg) values in patients at 2, 6, and 12 months after the operation. Results The number of125I radioactive particles implanted in 42 patients was 226, with an average of 14.5 (range 2.0–30.0) particles implanted per lesion. The local remission rates were 97.62% (41/42), 88.10% (37/42), and 85.71% (36/42) at 2, 6, and 12 months postoperatively, respectively. The volume of the lesions was (4.44 ± 1.57) cm3, (4.20 ± 1.70) cm3, and (4.23 ± 1.77) cm3at 2, 6, and 12 months after treatment, respectively, which significantly decreased from the preoperative baseline level of (6.87 ± 1.67) cm3(t-values: 9.466, 9.923, 7.566, all P<0.05). The Tg levels were 15.95 (5.45, 73.93) μg/L, 8.90 (2.20, 39.21) μg/L, and 6.00 (1.93, 14.18) μg/L at 2, 6, and 12 months after treatment, respectively, which were significantly lower than the preoperative baseline levels of 53.50 (20.94, 222.92) μg/L (Z values: -5.258, -5.009, -4.987, all P < 0.001). Postoperatively, Delivered to 90% of the GTV(D90) was slightly lower than the prescribed dose in 95.23% (40/42) of patients, but the difference was not statistically significant [(12,378.8 ± 3,182.0), (12,497.8 ± 1,686.4) cGy; t=0.251, P>0.05], and postoperative dose parameters delivered to 100% of the gross tumor volume (GTV)(D100) (6,881.5 ± 1,381.8) cGy, the volume percentages of GTV receiving 150% of the prescribed dose(V150) (58.5 ± 18.40)%) were lower than the preoperative plan D100 (8,085.8 ± 2,330.0) cGy, V150 (66.5 ± 17.70)%; t-value=8.913 and 3.032, both P<0.05; the remaining indicators were not significantly different from the preoperative plan (the differences in the number of implanted particles, Planning Target Volume(PTV), the volume percentages of GTV receiving 100% of the prescribed dose(V100), Homogeneity Index(HI)were not statistically significant (t/Z = -0.593, -1.604, 1.493, -0.663, all P>0.05). Conclusion Referring to the TPS preoperative plan, the125I particle implantation therapy for RAIR-DTC lymph node metastasis can achieve the expected dose distribution, ensuring precise short-term local tumor control efficacy.